Socio-cultural inhibitors to use of modern contraceptive techniques in rural Uganda: a qualitative study - Kabagenyi, Allen (Pan Afr Med J, 2016)
INTRODUCTION: Family planning is one of the cost-effective strategies in reducing maternal and child morbidity and mortality rates. Yet in Uganda, the contraceptive prevalence rate is only 30% among married women in conjunction with a persistently high fertility rate of 6.2 children per woman. These demographic indicators have contributed to a high population growth rate of over 3.2% annually. This study examines the role of socio-cultural inhibitions in the use of modern contraceptives in rural Uganda. METHODS: This was a qualitative study conducted in 2012 among men aged 15-64 and women aged 15-49 in the districts of Mpigi and Bugiri in rural Uganda. Eighteen selected focus group discussions (FGDs), each internally homogeneous, and eight in-depth interviews (IDIs) were conducted among men and women. Data were collected on sociocultural beliefs and practices, barriers to modern contraceptive use and perceptions of and attitudes to contraceptive use. All interviews were tape recoded, translated and transcribed verbatim. All the transcripts were coded, prearranged into categories and later analyzed using a latent content analysis approach, with support of ATLAS.ti qualitative software. Suitable quotations were used to provide in-depth explanations of the findings. RESULTS: Three themes central in hindering the uptake of modern contraceptives emerged: (i) persistence of socio-cultural beliefs and practices promoting births (such as polygamy, extending family lineage, replacement of the dead, gender-based violence, power relations and twin myths). (ii) Continued reliance on traditional family planning practices and (iii) misconceptions and fears about modern contraception. CONCLUSION: Sociocultural expectations and values attached to marriage, women and child bearing remain an impediment to using family planning methods. The study suggests a need to eradicate the cultural beliefs and practices that hinder people from using contraceptives, as well as a need to scale-up family planning services and sensitization at the grassroots.